2024
DOI: 10.3390/encyclopedia4010023
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Small-Scale Aquaponics Systems Using Artificial Intelligence and the IoT: Current Status, Challenges, and Opportunities

Abdul Aziz Channa,
Kamran Munir,
Mark Hansen
et al.

Abstract: Environment changes, water scarcity, soil depletion, and urbanisation are making it harder to produce food using traditional methods in various regions and countries. Aquaponics is emerging as a sustainable food production system that produces fish and plants in a closed-loop system. Aquaponics is not dependent on soil or external environmental factors. It uses fish waste to fertilise plants and can save up to 90–95% water. Aquaponics is an innovative system for growing food and is expected to be very promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Aquaponics could be a food production systems that permit a better understanding of water usage and water optimization using different hydroponic system designs for plant production [141,149,199]. The implementation of these system designs depend on the local space and characteristics, the availability of freshwater and the regional climate because of water evaporation (145).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaponics could be a food production systems that permit a better understanding of water usage and water optimization using different hydroponic system designs for plant production [141,149,199]. The implementation of these system designs depend on the local space and characteristics, the availability of freshwater and the regional climate because of water evaporation (145).…”
Section: Discussionmentioning
confidence: 99%
“…The most common aquaponic system design is based on water recirculation in a single loop between the fish tank and the hydroponic plant production system [147], also called coupled aquaponic systems using fish residues directly as plant nutrition [148]. Coupled aquaponic systems are characterized by their simple handling and production management, but it has been observed that one of the biggest challenges is the optimization of environmental and water quality conditions for fish and plant production due to the single loop recirculation system [149].…”
Section: Optimization Of Groundwater Employment In Aquaponic Food Pro...mentioning
confidence: 99%
“…Aquaponics could be a food production system that permits a better understanding of water usage and water optimization using different hydroponic system designs for plant production [140,148,197]. The implementation of these system designs depends on the local space and characteristics, the availability of freshwater, and the regional climate because of water evaporation [144].…”
Section: Discussionmentioning
confidence: 99%
“…The most common aquaponic system design is based on water recirculation in a single loop between the fish tank and the hydroponic plant production system [146], also called coupled aquaponic systems using fish residues directly as plant nutrition [147]. Coupled aquaponic systems are characterized by their simple handling and production management, but it has been observed that one of the biggest challenges is the optimization of environmental and water quality conditions for fish and plant production due to the single-loop recirculation system [148].…”
Section: Optimization Of Groundwater Employment In Aquaponic Food Pro...mentioning
confidence: 99%